Barwne epitety w liryce młodopolskiej na wybranych przykładach - Iwanowicz, Małgorzata (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2008)
The subject o f article arc colourful epithets in Mlodopolska’s Polish poetry on selected examples. Authoress concentrates her attention on picturcsqucs and decoratives epithets, with regard relcvance to important for this period theme of nature. She also considers their connection with such artistic trends like impressionism or secession, treats of most popular, nationals models for colour white, yellow, blue and red. She expresses conclusions for function of colourful epithets in Mlodopolska’s lyric texts.